The Use of a New Passive Sampler for Ozone and Nitrogen Oxides Monitoring in Ecological Effects Research - De Santis, Franco (ScientificWorldJournal, 2001)
A simple, cost-effective diffusive sampler is described that is suitable for measuring parts per billion (ppb) levels of ozone and nitrogen oxides. The diffusive sampler makes use of nitrite for ozone determination whereas for nitrogen oxides and nitrogen dioxide an active carbon tissue impregnated with sodium carbonate is used. Nitrate and nitrite, the formation of which is proportional to the pollutant concentration and sampling duration, are the two species analysed, respectively. Diffusion tubes have the advantage of being a low- cost, convenient way of mapping spatial distributions and investigating long-term trends of ozone and nitrogen oxides. The method is extremely useful for assessing long-term concentrations such as the annual mean for nitrogen oxides, as required by the Daughter Directive 1999/30/EC. Field tests to validate the method have been carried out at an urban background location with co-located passive samplers and continuous measurements of O(3) and NO(x) . An application in ecological effects monitoring for ozone is also presented.